3D-bioprinted silk fibroin-hydroxypropyl cellulose methacrylate porous scaffold with optimized performance for repairing articular cartilage defects. (January 2023) - Yan, Kai; Zhang, Xiao; Liu, Yang; Cheng, Jiangqi; Zhai, Chenjun; Shen, Kai; Liang, Wenwei; Fan, Weimin
Graphical abstract: Highlights: Silk fibroin-hydroxypropyl cellulose methacrylate (SF-HPCMA) bioink was configured for the first time. SF-HPCMA bioink exhibited good biocompatibility and rheological properties, which was suitable for 3D bioprinting. SF-HPCMA scaffolds were beneficial to cell proliferation and differentiation. The compression modulus of SF-HPCMA scaffolds reached that of normal articular cartilage. 3D bioprinted SF-HPCMA scaffolds could effectively repair articular cartilage defects in rabbits. Abstract: Repairing articular cartilage defects remains a clinical challenge. 3D bioprinting scaffolds to repair articular cartilage defects is a research hotspot nowadays. In this study, we used silk fibroin (SF) and hydroxypropyl cellulose methacrylate (HPCMA) to prepare a porous SF-HPCMA bioink capable of 3D bioprinting for the first time, and based on this bioink, we successfully bioprinted SF-HPCMA scaffolds with excellent mechanical properties. Scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), and rheological properties tests showed that SF-HPCMA bioink had suitable porosity, pore size, more β-sheets, and excellent rheological properties. The mechanical property measurement results showed that the compression modulus of SF-HPCMA scaffolds reached that of normal cartilage. In vitro experiments demonstrated that SF-HPCMA scaffolds were highly biocompatible and could effectively promote the proliferation and chondrogenic differentiation of BMSCs, and that the cartilage tissue produced by in vitro culture was of higher quality. At 12 weeks after implantation of SF-HPCMA scaffolds into the rabbit knee cartilage defects, the SF-HPCMA scaffolds could effectively repair the articular cartilage defects. SF-HPCMA bioink and scaffolds are promising materials for repairing articular cartilage defects.